Fulminant presentation of autoimmune hepatitis: clinical features and early predictors of corticosteroid treatment failure. Issue 6 (June 2015) - Mendizabal, Manuel; Marciano, Sebastián; Videla, María G.; Anders, Margarita; Zerega, Alina; Balderramo, Domingo C.; Tisi Baña, Matías R.; Barrabino, Martín; Gil, Octavio; Mastai, Ricardo; Yantorno, Silvina; Gadano, Adrián; et al.
Abstract : Background and aims: Classical features of autoimmune hepatitis (AIH) may be altered during the abrupt onset of the disease. Corticosteroid therapy can be life-saving, but its use in the fulminant presentation of AIH (F-AIH) remains controversial. We aimed to assess the clinical features of patients with F-AIH and to describe the role of corticosteroids in this population. Patients and methods: We retrospectively analyzed 154 adult patients with fulminant hepatic failure who were admitted to six liver transplantation (LT) programs. The AIH simplified criteria were used to identify patients with F-AIH. Results: We identified 40 (26%) patients with F-AIH. Compared with other etiologies, patients with F-AIH presented a longer interval from jaundice to encephalopathy (26 vs. 16 days, P =0.02) and a lower Model for End-Stage Liver Disease (MELD) score on admission (29 vs. 33, P =0.002). Overall, 25 (62%) patients with F-AIH underwent LT, eight (20%) patients survived, and seven (18%) died without LT. Seventeen patients received corticosteroids therapy, of whom seven (41%) survived without LT. Among the treated patients, higher MELD score and encephalopathy grade of 3 or more were associated significantly with corticosteroid failure. Conclusion: Patients with F-AIH have a more indolent presentation compared with the non-F-AIH population. Altogether, only eight (20%) patients presenting with F-AIH survived without LT. A subset of patients with F-AIH and an initial MELD score less than 27 and low-grade hepatic encephalopathy might benefit from administration of corticosteroids.